Truck Technology and Efficient Market Structure - Chiang, Judy S. Wang; Friedlaender, Ann F. (The Review of Economics and Statistics, 1985)
A bstractUsing the trucking industry as an example, this paper extends the empirical research on multiproduct firms to analyze the efficient numbers of firms in the industry. The paper first considers the issue of size related economies and argues that although there are limited economies of scale, economies of scope appear to be sufficiently strong to explain the observed large number of mergers and acquisitions that have occurred in the industry. The paper then considers the efficient number of firms in the industry. Using the concept of ray-average cost, it shows that for the output combinations observed in the industry, the efficient number of firms required to serve industry output is quite large.